A well-being promotion program increases self-compassion, active coping and emotion regulation among providers who work with children and families - Liliana J. Lengua; Rebecca Calhoun; Ignatius Balinbin; Robyn Long; Katie Malloy Spink; Marie Angeles (BMC Complementary Medicine and Therapies)
Abstract This study examined the effects of the REsilient Attitudes and Living for Professionals (REAL Pro) prevention intervention on the well-being of professionals who work with children and families. The program combines mindfulness and self-compassion practices with cognitive-behavioral tools that aim to promote improved stress management, emotion regulation and well-being, and was evaluated with early childhood (n = 87) and K-12 educators (n = 40), staff serving youth in out-of-school or after-school settings (n = 31), and medical providers (n = 35). Participants completed pre- and post-test assessments, reporting on measures of stress management (perceived stress, self-compassion), emotion regulation (dysregulation, active coping, denial), and well-being (flourishing, resilience, burnout, secondary trauma symptoms). Dependent sample t-tests were conducted, showing significant improvement from pre- to post-test in self-compassion, emotion regulation, active coping, and a trend toward increased resilience. Three-month follow-up in a small subset of the sample (n = 11) suggested potential delayed reduction in burnout and secondary trauma symptoms. Satisfaction surveys and qualitative data indicated high participant satisfaction with the program and that participants made use of and perceived benefits from the skills for themselves and their clients. The preventive intervention shows promise for providing professionals with tools for stress management and emotion regulation, with the potential for reducing burnout in providers working with children and families who tend to experience substantial work-related stress.